Disentangling the association between kidney function and atrial fibrillation: a bidirectional Mendelian randomization study. (15th May 2022) - Geurts, Sven; van der Burgh, Anna C.; Bos, Maxime M.; Ikram, M. Arfan; Stricker, Bruno H.C.; Deckers, Jaap W.; Hoorn, Ewout J.; Chaker, Layal; Kavousi, Maryam
Abstract: Background: The potential bidirectional causal association between kidney function and atrial fibrillation (AF) remains unclear. Methods: We conducted a bidirectional two-sample Mendelian randomization (MR) analysis. From multiple genome-wide association studies (GWAS), we retrieved genetic variants associated with kidney function (estimated glomerular filtration rate based on creatinine (eGFRcreat), blood urea nitrogen (BUN), chronic kidney disease (CKD stage ≥G3): n  = 1, 045, 620, eGFR based on cystatin C: n  = 24, 063-32, 861, urine albumin-to-creatinine ratio (UACR), and microalbuminuria: n  = 564, 257), and AF (n = 1, 030, 836). The inverse-variance weighted method was used as our main analysis. Results: MR analyses supported a causal effect of CKD ( n  = 9 SNPs, odds ratio (OR): 1.10, 95% confidence interval (CI): 1.04–1.17, p -value = 1.97 × 10 −03 ), and microalbuminuria ( n  = 5 SNPs, OR: 1.26, 95% CI: 1.10–1.46, p -value = 1.38 × 10 −03 ) on AF risk. We also observed a causal effect of AF on eGFRcreat ( n  = 97 SNPs, OR: 1.00, 95% CI: 1.00–1.00, p -value = 6.78 × 10 −03 ), CKD ( n  = 107 SNPs, OR: 1.06, 95% CI: 1.03–1.09, p-value = 2.97 × 10 −04 ), microalbuminuria ( n  = 83 SNPs, OR: 1.07, 95% CI: 1.04–1.09, p -value = 2.49 × 10 −08 ), and a suggestive causal effect on eGFRcys ( n  = 103 SNPs, OR: 0.99, 95% CI: 0.99–1.00, p-value = 4.61 × 10 −02 ). Sensitivity analyses, including weighted median estimator, MR-Egger, the MR pleiotropy residual sum and outlier test, and excluding genetic variants associated with possible confounders and/or horizontal mediators (myocardial infarction/coronary artery disease, heart failure) indicated that these findings were robust. Conclusions: Our results supported a bidirectional causal association between kidney function and AF. The shared genetic architecture between kidney dysfunction and AF might represent potential important therapeutic targets to prevent both conditions in the general population. Graphical abstract: Abbreviations: AF, atrial fibrillation; BUN, blood urea nitrogen; CKD, chronic kidney disease; creat, creatinine; cys, cystatin; eGFR, estimated glomerular filtration rate; GWAS, genome-wide association study; IVW, inverse variance weighted; MA, microalbuminuria; MR-PRESSO, Mendelian randomization pleiotropy residual sum and outlier; SNP, single nucleotide polymorphism; UACR, urine albumin-to-creatinine ratio; WME: weighted median estimator. *eGFRcreat, BUN, CKD GWAS n  = 1, 045, 620; eGFRcys GWAS n  = 24, 063-32, 861; UACR, MA GWAS n  = 564, 257. **AF GWAS n = 1, 030, 836. Unlabelled Image Highlights: The potential bidirectional causal association between kidney function and atrial fibrillation remains unclear. Genetic variants for kidney function and atrial fibrillation from genome-wide association studies were used in our analyses. Mendelian randomization analyses supported a bidirectional causal association between kidney function and atrial fibrillation. Kidney dysfunction and AF might represent therapeutic targets to prevent both conditions in the general population.